Clinico-Microbiological profile in dacryocystitis: a prospective observational study - Ragini Garg; Prabha Gupta; D.K. Shakya; Souryakant Varandani; Akanksha Uchainiya (International Journal of Medical Research and Review, 2018)
Introduction: Dacryocystit is is the inflammatory condition of the lacrimal sac which occur in acute and chronic form. Chronic dacryocystitis is commonly encountered, accounting for 87.1% of Epiphorawhich causes social embarrassment due to chronic watering from the eye. Understanding the antibiogram for micro organism causing inflammation of lacrimal sac can be useful in choosing the best antimicrobial. Hence the present study was done to evaluate the clinical profile and antibiogram of acute and chronic dacryocystitis.Method: A prospective observational study was done in patients with acute or chronic dacryocystitis attending ophthalmology OPD. Those fulfilling the eligibility criteria were enrolled in the study. Samples were collected from all the cases and were sent to microbiology lab for gram staining, culture and sensitivity.Result: 100 patients of dacryocystitis were enrolled, chronic dacryocystitis was found common than the acute dacryocystitis, along with a female (middle age group) preponderance. The main presenting symptom was watering (89%) followed by discharge (47%), swelling (34%), pain (23%) and tenderness (23%). Gram positive organisms (72.86%) were most commonly isolated. Among the Gram-positive organisms, Staph. aureus (37.14%) while Pseudomonas among Gram negative were the common isolate. Vancomycin and tobramycin are highly active against all Gram positive, tobramycin, gentamycin, fluoroquinolones and cephalosporins are found to be very active against Gram negative bacteria.Conclusion: The most common bacterial isolate in dacryocystitis, prevailing in this geographical area is Staphylococcus (Gram positive) followed by Pseudomonas, Pneumococcus and Staph epidermidis. Combination of Vancomycin and 3rd generation cephalosporin can be used as empirical therapy when the culture reports are awaited.